Knowledge and attitude towards dental insurance and utilization of dental services among insured and uninsured patients: A cross-sectional study - Radhika Maniyar; G K Umashankar (Wolters Kluwer Medknow Publications, 2018)
Aim: To assess the awareness and attitude towards dental insurance, and trends in utilization of dental services among insured and uninsured patients visiting a dental hospital in Bengaluru city. Materials and Methods: A cross-sectional study was conducted among 200 patients visiting Dental College in Bengaluru; of which, 100 patients were insured under Employees' State Insurance Scheme and 100 were uninsured. A face-to-face interview was carried out to collect information on sociodemographic data, knowledge, and attitude toward dental insurance and utilization of dental services among insured and uninsured groups. Collected data were analyzed using descriptive statistics and Chi-square test. Results: Among the insured group, only 29% had the knowledge about the total dental services covered in their insurance plan. Among the uninsured, only 4% were aware of the dental insurance integrated with health insurance plan. Dental treatment was perceived costly by 30% among insured and 81% among uninsured group. Among insured, 84% reported that dental insurance has benefitted them by reducing the financial burden and making the treatment easily available. Among uninsured, 74% believed that dental insurance can be beneficial to them. Statistical significant difference was obtained when overall attitudes among insured and uninsured groups were compared (P < 0.05). About 70.6% among insured and 49.3% among uninsured utilized dental services in the past 6-12 months. Conclusion: Knowledge regarding dental insurance was poor in both groups, while the insured group showed a more positive attitude toward benefits of dental insurance. Utilization of dental services was seen more among insured group.